Increased Surgical Complications but Improved Overall Survival with Adult Living Donor Compared to Deceased Donor Liver Transplantation: A Systematic Review and Meta-Analysis. (25th August 2020) - Tang, Wei; Qiu, Jian-Guo; Cai, Yang; Cheng, Luo; Du, Cheng-You
Abstract : Background . Living donor liver transplantation (LDLT) provides an alternative to deceased donor liver transplantation (DDLT) for patients with end-stage liver disease in the circumstance of scarcity of deceased grafts. However, the outcomes of LDLT remain controversial. Method . A systematic review and meta-analysis were performed to compare the outcomes of LDLT with DDLT. Twelve outcomes were assessed. Results . Thirty-nine studies involving 38563 patients were included. LDLT was comparable in red blood cell transfusion, perioperative mortality, length of hospital stay, retransplantation rate, hepatitis C virus recurrence rate, and hepatocellular carcinoma recurrence rate with DDLT. Cold ischemia time was shorter and duration of recipient operation was longer in LDLT. Postoperative intra-abdominal bleeding rate occurred less frequently in LDLT recipients (odds   ratio   OR = 0.64, 95 % confidence   interval   CI = 0.46 − 0.88, P = 0.006 ), but this did not decrease the perioperative mortality. LDLT was associated with significantly higher biliary (OR = 2.23, 95 % CI = 1.59 − 3.13, P < 0.00001 ) and vascular (OR = 2.00, 95 % CI = 1.31 − 3.07, P = 0.001 ) complication rates and better overall survival (OS) (1 year: OR = 1.32, 95 % CI = 1.01 − 1.72, P = 0.04 ; 3 years: OR = 1.39, 95 % CI = 1.14 − 1.69, P = 0.0010 ; and 5 years: OR = 1.33, 95 % CI = 1.04 − 1.70, P = 0.02 ). According to subgroup analysis, biliary complication rate and OS improved dramatically as experience increased, while vascular complication rate could not be improved because it was mainly caused by the difference of the donor type itself. Conclusions . LDLT remains a valuable option for patients in need of liver transplantation for it provides an excellent alternative to DDLT without compromising recipient outcomes. Further refinement in biliary and vascular reconstruction techniques and the accumulation of liver transplantation centers' experience are the key factors in expanding the application of LDLT.